2021
DOI: 10.3390/medicina57111259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sugammadex for the Reversal of Rocuronium-Induced Neuromuscular Blockade in Patients with End-Stage Renal Disease: A Systematic Review and Meta-Analysis

Abstract: Background and Objectives: Sugammadex is widely used in anesthesia to reverse rocuronium-induced neuromuscular blockade (NMB). In patients with compromised kidney function, most drugs show alteration of their pharmacokinetic profile with reduced clearance. The purpose of this article is to examine the efficacy, pharmacokinetics, and safety of sugammadex in end-stage renal disease (ESRD) patients receiving general anesthesia, using a systematic review. Materials and Methods: The databases of PubMed, EMBASE, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(58 reference statements)
0
11
0
1
Order By: Relevance
“…A recent systematic review article with a meta-analysis showed that sugammadex may effectively and safely reverse rocuronium-induced neuromuscular blockade in patients with end-stage renal disease. 5 We read the comments by the authors on our study with interest and we agree that further investigation is necessary.…”
mentioning
confidence: 76%
“…A recent systematic review article with a meta-analysis showed that sugammadex may effectively and safely reverse rocuronium-induced neuromuscular blockade in patients with end-stage renal disease. 5 We read the comments by the authors on our study with interest and we agree that further investigation is necessary.…”
mentioning
confidence: 76%
“…A recently published systematic review found that the time required to reach a TOF ratio ≥ 0.9, 0.8, or 0.7 was significantly longer in patients with ESRD. The plasma clearance of sugammadex in patients with ESRD was significantly lower than that in healthy controls, based on meta-analysis of six prospective observational studies [ 4 ]. However, given that the difference in the recovery time is not long enough to cause a clinically significant difference (e.g., the mean difference of the time to reach a TOF ratio of 0.9:1.14 min), it is believed that the NMB reversal time in patients with ESRD is slightly longer than that in patients with normal renal function.…”
Section: Efficacy Of Sugammadex In Patients With Esrdmentioning
confidence: 99%
“…Total plasma clearance of sugammadex in patients with ESRD was significantly lower than that in healthy controls [ 7 , 10 ]. Total plasma clearance of rocuronium in patients with ESRD was significantly lower than that in healthy controls [ 4 ]. Additionally, the effect of renal impairment on total plasma clearance was found to be greater with sugammadex than with rocuronium [ 7 ].…”
Section: Pharmacokinetic Assessment Of Sugammadex In Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…None of them were due to the recurrence of NMB. Although some studies have investigated the efficacy and safety of sugammadex use in ESRD patients [ 61 , 62 ], evidence regarding the effect on PPCs in ESRD patients is insufficient, and more data and research are required.…”
Section: Recent Researches In Specific Patient Populations or Surgeriesmentioning
confidence: 99%